A review on advanced microencapsulation technology to enhance bioavailability of phenolic compounds: Based on its activity in the treatment of Type 2 Diabetes. (March 2019) - Chen, Lei; Gnanaraj, Charles; Arulselvan, Palanisamy; El-Seedi, Hesham; Teng, Hui
Abstract: Background: Studies on and the application of polyphenolic compounds, have recently attracted great interest in the functional foods due to their potential health benefits to humans. However, the major disadvantage associated with phenolic compounds is their constrained bioavailability, mainly caused by its low aqueous solubility, poor stability and limited membrane permeability. Scope and approach: The aim of this study is to give an overview of the microencapsulation technology to enhance bioavailability of phenolic compounds. Furthermore, the anti-diabetic effect of microencapsulated phenolic compounds and capability of them to produce new functional foods will be discussed. Key findings and conclusions: The utilization of microencapsulated polyphenols, instead of free compounds, can effectively alleviate the deficiencies. This review provided valuable insight that may be useful for identifying trends in the commercialization of microencapsulation -technological products or for identifying new research areas. The results published to date confirm that the encapsulation promotes the protection of active compounds, enabling industrial applications of active packaging. Highlights: Relevance of advanced microencapsulation technologyand applications on phenolics is presented. Enhance bioavailability of phenolic using microencapsulation are described. Phenolics using microencapsulation in treatment of Type 2 Diabetes are discussed.